2008
DOI: 10.1002/cncr.23912
|View full text |Cite
|
Sign up to set email alerts
|

Bone mineral density in young adult survivors of acute lymphoblastic leukemia

Abstract: BACKGROUND.The purpose of the current study was to determine the prevalence of low bone mineral density (BMD) (ie, osteopenia) and identify factors associated with low BMD in young adult survivors of childhood acute lymphoblastic leukemia (ALL).METHODS.Dual energy x‐ray absorptiometry was used to evaluate BMD in 74 randomly selected, long‐term childhood ALL survivors initially treated in Minneapolis/St. Paul, Minnesota. Growth hormone (GH)‐releasing hormone–arginine stimulation testing was conducted to evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
55
1
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(58 citation statements)
references
References 114 publications
1
55
1
1
Order By: Relevance
“…Previous studies have shown that among adult ALL survivors, hormonal deficiencies, hypogonadism, insulin resistance, and dyslipidemia are prevalent (3,4,5,6). Low bone mineral density (BMD) and osteoporosis are also recognized complications of ALL, and according to some studies, adverse skeletal effects may persist until adulthood (7,8,9,10,11,12).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that among adult ALL survivors, hormonal deficiencies, hypogonadism, insulin resistance, and dyslipidemia are prevalent (3,4,5,6). Low bone mineral density (BMD) and osteoporosis are also recognized complications of ALL, and according to some studies, adverse skeletal effects may persist until adulthood (7,8,9,10,11,12).…”
Section: Introductionmentioning
confidence: 99%
“…As an increasing number of cancer survivors reaches adulthood, there may be consequences of the treatment, including adiposity, metabolic syndrome traits [2][3][4][5][6][7][8][9] and occasionally low bone mass [10][11][12][13][14][15][16][17][18], which is a condition not totally understood, so far.…”
Section: Introductionmentioning
confidence: 99%
“…Cancer survivors, particularly ALL patients, are part of one of these important groups and there are several important concerns regarding their bone heath [10][11][12][13][14][15][16][17][18][19]. Low bone mass has been observed in all phases of the disease: at diagnosis, during treatment, and throughout the post-treatment period for as long as 20 years [21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Screening for low body mineral density is recommended for survivors treated with hematopoietic stem cell transplant, methotrexate, and steroids. Problems with growth [4], weight [5], puberty and gonadal function [6], bone health [7], thyroid function [8], and adrenal function [9] have been described.…”
Section: Introductionmentioning
confidence: 99%